Time to achieving therapeutic international normalized ratio increases hospital length of stay after heart valve replacement surgery - Arendt, Christopher J.; Hong, Joon Hwa; Daly, Richard C.; Scott, Christopher; Mehta, Ramila A.; Bailey, Kent; Pathak, Jyotishman; Pereira, Naveen L. (The American heart journal, 2017)
Achieving a therapeutic international normalized ratio (INR) before hospital discharge is an important inpatient goal for patients undergoing mechanical cardiac valve replacement (MCVR). The use of clinical algorithms has reduced the time to achieve therapeutic INR (TTI) with warfarin therapy. Whether TTI prolongs length of stay (LOS) is unknown. Patients who underwent MCVR over a consecutive 42-month period were included. Clinical data were obtained from the Society of Thoracic Surgeons Adult Cardiac Surgery database and electronic medical records. Therapeutic INR was defined as per standard guidelines. Warfarin dose was prescribed using an inpatient pharmacy-managed algorithm and computer-based dosing tool. International normalized ratio trajectory, procedural needs, and drug interactions were included in warfarin dose determination. There were 708 patients who underwent MCVR, of which 159 were excluded for reasons that would preclude or interrupt warfarin use. Among the remainder of 549 patients, the average LOS was 6.4days and mean TTI was 3.5days. Landmark analysis showed that subjects in hospital on day 4 (n=542) who achieved therapeutic INR were more likely to be discharged by day 6 compared with those who did not achieve therapeutic INR (75% vs 59%, P<.001). Multivariable proportional hazards regression with TTI as a time-dependent effect showed a strong association with discharge (P=.0096, hazard ratio1.3) after adjustment for other significant clinical covariates. Time to achieve therapeutic INR is an independent predictor of LOS in patients requiring anticoagulation with warfarin after MCVR surgery. Alternative dosing and anticoagulation strategies will need to be adopted to reduce LOS in these patients.